Association between Gene Polymorphism of Manganese Superoxide Dismutase and Prostate Cancer Risk. Issue 3 (11th January 2013) - Eken, Ayşe; Erdem, Onur; Arsova‐Sarafinovska, Zorica; Akay, Cemal; Sayal, Ahmet; Matevska, Nadica; Suturkova, Ljubica; Erten, Koray; Özgök, Yaşar; Dimovski, Aleksandar; Aydin, Ahmet
ABSTRACT Manganese superoxide dismutase (MnSOD) is the most effective antioxidant enzyme in mitochondria and protects cells from reactive oxygen species‐induced oxidative damage. The aim of this study was to investigate the association between MnSOD Ala‐9Val gene polymorphism and prostate cancer (PCa) risk in Turkish men with prostate cancer. 33 patients with PCa and 81 control individuals were included in the study. We observed an association between MnSOD Ala/Ala frequency and a higher PCa risk. In addition, we found that the increased risk of early‐onset PCa (under age of 65) in the men homozygous for Ala allele was higher than the men homozygous for Val allele. However, we determined that MnSOD Ala‐9Val genotype was not associated with the aggressiveness of the disease. The results of our study suggest that MnSOD Ala/Ala genotype may influence on early‐onset of PCa patients, but no effect on subsequent development of the disease in Turkish men. However, our study has a limitation that is small numbers of individuals for cases and controls. Therefore, the presented study limited our statistical power to fully investigate the gene polymorphism on cancer risk. © 2013 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:213‐218, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21472